Efeitos da gameterapia e do treinamento funcional no equilíbrio e na funcionalidade em pacientes com doença de Parkinson - Fontes, Patrícia Almeida (2018)
Introduction: Parkinson's disease is a degenerative, idiopathic neurological disease, that is, of unknown origin. It is characterized by decreased production of the dopamine neurotransmitter, located predominantly in the substantia nigra and in regions of the brain involved with motor function. Physical exercises in Parkinson's disease favor the performance of functional activities such as: sit, stand up, walk, as well as reduce bradykinesia, postural instability and falls index. Objectives: The objectives of this dissertation were: (1) Systematic review of the literature to identify the most used balance evaluation instruments in individuals with Parkinson's disease; (2) evaluate and compare the effects of physical exercise through game therapy and functional training in the balance and functionality of individuals with Parkinson's disease. Results: (1) Five methods are worth mentioning because they have been the most used and most sensitive in assessing the balance of individuals with Parkinson's disease (Time Balance, (2) It was observed that physical exercise through game therapy and functional training proved to be efficient for the improvement of the balance and functionality of individuals with Parkinson's disease.Conclusions: that there is a great variety of tests in the literature that seek to measure the balance, but four are the methods that deserve to be highlighted because they have been the most used and most sensitive in assessing the balance of individuals with Parkinson's disease.And that physical exercise through game therapy and functional training has proved to be effective in improving the balance and functionality of individuals with Parkinson's disease, suggesting er a viable therapeutical alternative for the treatment of this pathology.